Nepalese Tax Structure: An Analytical Perspective - Khanal, Madhav (JMC Research Journal, 2018)
Tax is the major source of revenue for the government, and development of any country’s economy largely depends on the tax structure it has adopted. A Tax structure which facilitates easy business and leaves no chance for tax evasion brings prosperity to a country’s economy. On the other hand, tax structure that has provisions for tax evasion and the one which does not facilitate ease of doing business shows down the economic growth. Nepal has a well-developed tax structure. The power to levy taxes and duties is distributed among the three tiers of the Government, in accordance to the constitutional provisions. Nepali tax system has gone through many reforms but still it is very far from being an ideal one. Many problems like tax evasion, reliance on indirect taxes, black money and existence of parallel economy show that Nepali tax system requires some major reforms in the future ahead to address all this problem. This study is purely based on secondary data. Various figures are obtained from different sources of the government of Nepal. It is seen that there is major dependence on indirect taxes than the direct taxes.